Gender, transactional sex, and HIV prevention cascade engagement among urban refugee and displaced adolescents and youth in Kampala, Uganda. Issue 7 (3rd July 2021) - Logie, Carmen Helen; Okumu, Moses; Mwima, Simon; Hakiza, Robert; Abela, Heather; Kyambadde, Peter
ABSTRACT: HIV prevention needs among urban refugee and displaced youth engaged in transactional sex are understudied. We examined associations between transactional sex and the HIV prevention cascade among urban refugee/displaced youth in Kampala, Uganda. We conducted a cross-sectional survey with a peer-driven sample of refugee/displaced adolescent girls and young women ( n = 324) and adolescent boys and young men ( n = 88) aged 16–24 living in Kampala's informal settlements. We conducted gender-disaggregated multivariable linear and logistic regressions to examine associations between past 12-month transactional sex and: lifetime HIV testing, condom self-efficacy, and recent [past 3-month] consistent condom use. Among the 27% of young women reporting transactional sex, 63% reported HIV testing. In multivariable analyses with young women, transactional sex was associated with higher condom self-efficacy, increased consistent condom use, but not HIV testing. Among the 48% of young men reporting transactional sex, 50% reported HIV testing. In multivariable analyses with young men, transactional sex was associated with lower HIV testing but not with condom self-efficacy or consistent condom use. Young men were 68% less likely to report HIV testing if transactional sex engaged. Findings point to urgent HIV testing gaps among transactional sex engaged urban refugee/displaced youth and a need for gender-tailored HIV prevention strategies.